Sexual rights and sexual pleasure: Sustainable Development Goals and the omitted dimensions of the leave no one behind sexual health agenda - Logie, Carmen H. (Global public health, 2023)
This commentary explores the missing discourse of sexual rights and sexual pleasure in the Sustainable Development Goals (SDG) that purport to leave no one behind. The SDG propose a welcome focus on sexual health and human rights for all, expanding beyond the Millennium Development Goals. While promising in many ways for advancing global sexual and reproductive health, and reproductive rights, the omission of sexual rights is troubling. So too is the erasure of lesbian, gay, bisexual, transgender and queer (LGBTQ) persons, and sex workers, from the SDG discussions of social inequities. Illustrative examples are provided to demonstrate how a sexual rights focus could advance SDG 3 focused on healthy lives and well-being for all. First, sexual rights are presented as integral to realizing Target 3.3's focus on ending the HIV pandemic among LGBTQ persons and sex workers (and LGBTQ sex workers). Second, sexual pleasure is introduced as an integral component of sexual health and sexual rights that could facilitate the realization of Target 3.7's aim to provide universal access to sexual and reproductive health information and education. To truly leave no one behind and realize sexual health for all, the SDG need to begin from a foundation of sexual rights.